Sensitivity of soil organic matter decomposition to temperature at different depths in permafrost regions on the northern Qinghai‐Tibet Plateau. (3rd October 2016) - Mu, C.; Zhang, T.; Zhang, X.; Cao, B.; Peng, X.
Abstract : The temperature sensitivity coefficient (Q10 ) of soil organic matter decomposition is an important variable for global climate models. Permafrost regions contain large organic carbon pools. A deep core was taken in permafrost from the northern Qinghai‐Tibet Plateau (QTP) and exposed to increases in temperature below and above 0°C. The production of CO2 was related to the soil organic carbon (SOC) contents and stable carbon isotopes. Smaller values of δ 13 C‐SOC and δ 13 C‐CO2 showed that the release of CO2 was primarily from soil with large SOC contents. The sensitivities of soil organic matter (SOM) decomposition to temperature near to the permafrost table and in some permafrost layers were larger than those in other layers. In some layers, a temperature increase below 0°C had a greater effect on the decomposition of SOM than one above 0°C. The values of Q10 in active layers varied from 2.7 to 23.0, with a mean of 8.8. The values of Q10 were larger in the deeper layers; they varied from 1.6 to 49.4, with a mean of 20.8. This is because the degradation of permafrost is usually associated with an increase in temperature even when the soil is in a frozen state. Our results suggest that the large values of Q10 at depth under frozen conditions merit more consideration of the response of SOC to climate warming in future research. Highlights: The sensitivity to temperature coefficient, Q10, is an important property for global climate models. The values of Q10 for soil organic matter decomposition were also large in deep layers. A temperature increase below 0°C has large effects on Q10 . The large values of Q10 at depth under frozen conditions merit more consideration.